Effect of Debittering with Different Solvents and Ultrasound on Carotenoids, Tocopherols, and Phenolics of Lupinus albus Seeds - Lorenzo Estivi; Davide Fusi; Andrea Brandolini; Alyssa Hidalgo (MDPI AG, 2022)
Lupin seeds represent a rich nutritional source of bioactive compounds, including antioxidant molecules such as carotenoids, tocopherols, and phenolics. However, before consumption, the lupin seeds must be debittered in order to remove their bitter and toxic alkaloids. This study analyzed the impact on the bioactive compounds of Lupinus albus seeds of a recent time- and water-saving debittering method, which employs alternative washing solutions (0.5% or 1% of either NaCl or citric acid), with or without the assistance of ultrasound. The results were compared with those of two control methods using water or a NaCl solution. The sonication, when it was significant, led to a large loss of bioactive compounds, which was most likely due to its extraction capability. The seeds that were debittered without ultrasound presented high concentrations of tocopherols (172.8-241.3 mg/kg DM), carotenoids (10.9-25.1 mg/kg DM), and soluble-free (106.9-361.1 mg/kg DM), soluble-conjugated (93.9-118.9 mg/kg DM), and insoluble-bound (59.2-156.7 mg/kg DM) phenolics. The soluble-free fraction showed the greatest loss after a prolonged treatment. Overall, debittering with citric acid or NaCl preserved the highest concentration of antioxidant compounds by shortening the treatment time, thus preventing extensive leaching.